Genomic adaptation of the picoeukaryote Pelagomonas calceolata to iron-poor oceans revealed by a chromosome-scale genome sequence - Nina Guérin; Marta Ciccarella; Elisa Flamant; Paul Frémont; Sophie Mangenot; Benjamin Istace; Benjamin Noel; Caroline Belser; Laurie Bertrand; Karine Labadie; Corinne Cruaud; Sarah Romac; et al. (Communications Biology, 2022)
Genomic inference reveals potential climate change-driven range expansion of the phytoplankton species Pelagomonas calceolata.